Restoring endodontically treated teeth with all-ceramic endo-crowns: Case report - Veselinović Valentina; Todorović Aleksandar; Lisjak Dejan; Lazić Vojkan (Serbian Medical Society - Dental Section, Belgrade, 2008)
The all-ceramic endocrowns are one piece restoration used in the therapy of endodontically treated teeth, usually, with a decreased vertical dimension of the tooth crown. The aim of this paper is to describe two techniques of the making of endocrowns using case studies and to present the advantages and disadvantages of both techniques by way of their comparison. Chair-side production with the Cerec CAD-CAM system and pressing of the ceramic with the Empres II system was used for the production of the endocrowns. Cerec CAD-CAM and Empres II systems yielded equally good results in the production of the endocrowns, in terms of their functionality, retention, aesthetic and duration. The basic difference between them is the length of the endocrown production procedure as the Cerec CAD-CAM system makes it possible to apply the treatment during a single visit using a wide range of materials....